Theoretical Analysis of a Rectifying Gap Junction Model - Hu, X. L.; Zhang, Y. T.; Bao, J. L. (Methods of Information in Medicine, 2000)
Based on the experimental observations, an electrical circuitry model for a rectifying gap junction was developed in previous work. In order to show the physiological function for each element in the model, a theoretical analysis is carried out in this report. The results indicate that the gap junctional capacitance Cj newly introduced into the model plays a major role in determining the duration increase, the peak attenuation, and the peak delay on the postmembrane action potential. Also, a comparison between the newly proposed model and the widely accepted kinetic model by Giaume is made. The results show that the electrical circuitry model can not only describe the characteristics of Giaume’s model but also allow the interpretation of some experimental phenomena that were not reflected in other gap junctional models.
Keywords: Gap Junction Model